Presenting and Linking Grammatical Data on the Franček Educational Language Portal - Ledinek, Nina; Ahačič, Kozma; Petric Žižić, Špela (Slovenski jezik / Slovene Linguistic Studies, 2023)
This article presents how grammatical data are treated and presented in the first specialized lexicographic and grammatical learning e-tool for Slovenian, the Franček portal, and how these data are linked across the portal’s dictionary, advisory, and teaching components. By displaying grammatical material in an innovative manner and linking it effectively, this interactive portal—which offers reliable content and is designed following modern educational principles—is intended to contribute to motivating students to learn grammatical material. The article also draws attention to the fact that effectively linking grammatical data on the portal can play an important role in the development of language teaching and influence the methodology of language resource design.